The productivity impact of the digitally connected 5 - layer stack in manufacturing enterprises - del Castillo, Adolfo Crespo; Patsavellas, John; Salonitis, Konstantinos; Emmanouilidis, Christos (Elsevier, 2021)
This paper investigates the application of modern industrial internet protocols and network architecture in manufacturing companies, from the perspectives of productivity and sustainability, framed in the fourth industrial revolution paradigm. This is achieved by delving into the existing information systems and devices, their inter-operability and interconnections using industrial internet of things protocols. The paper details a study generating a standard model of data architecture to better unify the different layers of the information systems that typify most manufacturing companies, leveraging their existing digital infrastructure to establish a solid base for further digitalization.
Keywords: Industry 4.0; Industrial Internet of Things (IIoT); MQTT; Manufacturing Execution System (MES); SCADA; Enterprise Scalable Data Architecture (ESDA); Overall Equipment Efficiency (OEE); Self-Cleaning-Data